ANALISIS REAKSI PASAR ATAS PENGUMUMAN STOCK SPLIT OLEH PT. PP LONDON SUMATRA INDONESIA TBK TAHUN 2011 - Mahesa Priadanta Putra; Djuma hir (Jurnal Ilmiah Mahasiswa FEB, 2012)
The decision to stock split is usually done when the stock price is overvalued so it will reduce the interest of investors to buy it. Stock split arise or occur in the stock market because of the willingness of the issuer to maintain that its shares remain in a trading range is optimal. Experts said the stock split as a cosmetics stock, in the sense that the action is an effort polishing company stock to make it more attractive to investors even though no increase prosperity for investors. Companies that made ​​the object of this study is that PT PP London Sumatra Indonesia on the Indonesian Stock Exchange (IDX) during 2011. In this study, the variable used is TVA, and abnormal return. This study analyzes the results of the overall stock split events on PT PP London Sumatra Indonesia in Indonesian Stock Exchange during the five days before and five days after the event does not have a significant impact on TVA, and abnormal return between before and after the stock split event, so we get that stock split on companies listed on the Stock Exchange does not have a high content of useful information for investors in making decisions sale and purchase of shares in other words, the stock market does not react significantly to the occurrence of excess stock split . Therefore companies need to consider the factors the backdrop that such strong dominance of external factors such as political and economic instability Indonesia rather than internal factors which impact on market sentiment, and the issues that can affect the market reaction Keywords: stock splits, trading volume activity, and abnormal return